A Potential Collective Defense of Drosophila Larvae Against the Invasion of a Harmful Fungus - Trienens, Monika; Rohlfs, Marko (Frontiers in Ecology and Evolution, 2020)
The establishment of a collective defence is an important means of controlling the spread of harmful microbes in group-living animals. Collective defences are associated with costs resulting from the investment in resources and risk taking of infections or exposure to microbial toxins for the performing individual and are often assumed to have evolved in (eu)social insects, like bees and ants, as a result of close contact and pathogen transmission between nest mates. We hypothesise that collective antimicrobial defence mechanisms are potentially also found in insects that exhibit simpler forms of sociality or even mere aggregation behaviour. Larvae of the saprophagous fruit fly Drosophila melanogaster develop in high-density aggregations on rotting fruits, which are often colonized by insecticidal filamentous fungi. Here we show that fruit fly larvae suppress the invasion of a harmful fungus not only by the summative effect of individuals at high densities, but also that larger groups of larvae at the same density can control fungal growth more efficiently. We achieved the necessary manipulation of the group size by increasing the number of larvae in proportion to an increase in habitat size, thereby excluding the effect of density changes on fungal growth as a confounding factor. We found evidence that part of the variation in the ability to suppress the fungus in this group size dependent manner can be explained by genetic variation at the insects’ foraging locus (for). Group size therefore influences the extent to which the larval aggregates suppress the spread of a harmful fungus. This indicates a potential collective defence against habitat invasion by pathogenic fungi. Selection pressure on the efficiency of this potential defence strategy may contribute to the evolution of aggregation behaviour in non-(eu)social insects.